The political economy of regulatory risk - Roland Strausz (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper investigates political uncertainty as a source of regulatory risk. It shows that political parties have incentives to reduce regulatory risk actively: Mutually beneficial pre-electoral agreements that reduce regulatory risk always exist. Agreements that fully eliminate it exist when political divergence is small or electoral uncertainty is appropriately skewed. These results follow from a fluctuation effect of regulatory risk that hurts parties and an output-expansion effect that benefits at most one party. Due to commitment problems, regulatory agencies with some degree of political independence are needed to implement pre-electoral agreements.
Keywords: D82; 330; regulation; regulatory risk; political economy; electoral uncertainty; independent regulatory agency; Regulierung; Politische Entscheidung; Risiko; Aufsichtsbehörde; Selbstverwaltung; Public Choice; Theorie